2007
DOI: 10.1177/0883911507082157
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Nanofibrils Linked to Chitosan Glycolate as Spray, Gel, and Gauze Preparations for Wound Repair

Abstract: Recent advances in process chemistry have made it possible to make chitosan and chitin nanofibril materials more flexible and useful for the development of new biorelated products. In this study, the effectiveness of three chitin nanofibril/chitosan glycolate-based preparations, a spray (Chit-A), a gel (Chit-B), and a gauze (Chit-C), in healing cutaneous lesions are assessed macroscopically and by light microscopy immunohistochemistry. These evaluations are compared to the results obtained using a laser co-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…This property of CN-based composites has been shown to be significant in the modulation of cell behaviour during tissue regeneration [23][24][25]. It seems possible that positively-charged CN, interacting with negatively charged glycosaminoglycans and proteoglycans, fundamental components of the ECM, may have an important role in tissue regeneration.…”
Section: Chitin Nanofibril-hyaluronic Acid Nanoparticlesmentioning
confidence: 99%
“…This property of CN-based composites has been shown to be significant in the modulation of cell behaviour during tissue regeneration [23][24][25]. It seems possible that positively-charged CN, interacting with negatively charged glycosaminoglycans and proteoglycans, fundamental components of the ECM, may have an important role in tissue regeneration.…”
Section: Chitin Nanofibril-hyaluronic Acid Nanoparticlesmentioning
confidence: 99%
“…(Figure 3) [14][15][16]. This product quickly causes the alteration of the pathogenic micro-organisms membrane, while it promotes a better and regular collagen production (Figure 4).…”
Section: Wound Healing and Anti-bacterial Activitiesmentioning
confidence: 99%
“…Differently from the chitin powder and according to a newly patented easy process, in fact, many chemical and natural ingredients can be complexed by this crystal-like polysaccharide and then released into the skin/body, at appropriate sites and under certain conditions, without harmful side effects, possessing interesting new biological properties also [8][9][10][11][12][13]. For all these reasons these innovative pure nano-crystallites and their derivatives have been studied to verify their activity in many industrial and biomedical applications [14][15][16][17][18] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown many promising properties of these nanoparticles which include keratinocyte and fibroblast proliferation; regulation of collagen synthesis; cytokine and macrophage secretion [80,81]. Apart from these, chitin nanofibrils have been shown to promote wound healing [82,83]. …”
mentioning
confidence: 99%